2017
DOI: 10.1111/1753-0407.12584
|View full text |Cite
|
Sign up to set email alerts
|

Optimism, pessimism, cynical hostility, and biomarkers of metabolic function in the Women's Health Initiative

Abstract: In multivariable models, higher dispositional pessimism was associated with worse metabolic function; these findings were not modified by obesity status. Results extend prior work by linking pessimism to an objective biomarker of insulin resistance in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 97 publications
(156 reference statements)
0
25
0
Order By: Relevance
“…Pessimism has been linked to higher ambulatory blood pressure and greater daily experience of stress (Raikkonen, Matthews, Flory, Owens, & Gump, 1999). Pessimism has been linked to higher fasting insulin (Tindle et al, 2017), unhealthy lipid profiles (Boehm, Williams, Rimm, Ryff, & Kubzansky, 2013) and inflammatory biomarkers (Roy et al, 2010). It has also been suggested that optimism is associated with reduced hypothalamus-pituitary-adrenal axis reactivity (Chida & Hamer, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pessimism has been linked to higher ambulatory blood pressure and greater daily experience of stress (Raikkonen, Matthews, Flory, Owens, & Gump, 1999). Pessimism has been linked to higher fasting insulin (Tindle et al, 2017), unhealthy lipid profiles (Boehm, Williams, Rimm, Ryff, & Kubzansky, 2013) and inflammatory biomarkers (Roy et al, 2010). It has also been suggested that optimism is associated with reduced hypothalamus-pituitary-adrenal axis reactivity (Chida & Hamer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Optimism appears to have a moderating role in the association between feelings of loss of hope and suicidal ideation (Hirsch & Conner, 2006). Several studies have found that optimism is associated with better physical health (Cauley et al, 2017;Matthews et al, 2004;Segovia, Moore, Linnville, & Hoyt, 2015;Tindle et al, 2017) and mental health (Brissette, Scheier, & Carver, 2002;Schou et al, 2004;Segovia et al, 2015;Shnek, Irvine, Stewart, & Abbey, 2001), although there are some exceptions (Gallagher et al, 2013). A recent study by Kim et al (2017) found an association between lower levels of optimism and mortality due to heart disease, stroke, respiratory disease and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Significant associations between psychological attitudes and important health outcomes have been documented ( Progovac et al, 2017 , Puig-Perez et al, 2017 , Tindle et al, 2017 ). In this analysis we present findings based on quartile scores ( Tindle et al, 2009 , Hingle et al, 2014 , Yan et al, 2003 , Iribarren et al, 2000 , Scherwitz et al, 1992 ) for optimism and cynical hostility.…”
Section: Methodsmentioning
confidence: 99%
“…Their study reported that among 7,800 British men and women, optimism was not associated with incidence diabetes; however, significant associations between diabetes, life satisfaction, and emotional vitality were found. In a racially and ethnically diverse sample of 3,443 post-menopausal women, Tindle et al 29 found that optimism was negatively associated with insulin resistance in unadjusted analyses, but the association was not significant after adjustment for clinical factors and depressive symptoms. In our study, optimism was only associated with a lower prevalence of diabetes among men after adjustment for age.…”
Section: Optimismmentioning
confidence: 99%